Prehospital and in-hospital delays to care and associated factors in patients with STEMI: an observational study in 101 non-PCI hospitals in China - Min Li; Yangfeng Wu; Xian Li; Wuxiang Xie; Lin Feng; Aihua Zhang; Licheng Lei; R Gao (BMJ Open)
Objectives To describe the prehospital and in-hospital delays to care and factors associated with the delays among patients with ST-segment elevation myocardial infarction (STEMI) in non-percutaneous coronary intervention (PCI) hospitals in China.Design, setting and participants We analysed data from a large registry-based quality of care improvement trial conducted from 2011 to 2014 among 101 non-PCI hospitals in China. A total of 7312 patients with STEMI were included. Prehospital delay was defined as time from symptom onset to hospital arrival >120 min, first ECG delay as time from arrival to first ECG >10 min, thrombolytic therapy delay as time from first ECG to thrombolytic therapy >10 min and in-hospital delay as time from arrival to thrombolytic therapy >30 min. Logistic regressions with generalised estimating equations were preformed to identify the factors associated with each delay.Results The rates of prehospital delay, first ECG delay, thrombolytic therapy delay and in-hospital delay were 67.1%, 31.4%, 85.8% and 67.8%, respectively. Patients who were female, older than 65 years old, illiterate, farmers, onset during late night and forenoon, had heart rate ≥100 beats/m at admission were more likely and patients who had history of myocardial infarction, hypertension or SBP <90 mm Hg at admission were less likely to have prehospital delay. First ECG delay was more likely to take place in patients arriving on regular hours. Thrombolytic therapy delay rate was lower in patients who had prehospital delay or first ECG delay but higher in those with heart rate ≥100 beats/m at admission. In-hospital delay rate was lower in patients with a history of dyslipidaemia and those who arrived during regular hours.Conclusion Chinese patients with STEMI in low medical resource areas suffered severe prehospital and in-hospital delays to care. Future efforts should be made to improve the prehospital delay among vulnerable populations with low socioeconomic status.Trial registration number NCT01398228; Post-results.